Knowledge, attitude, and practice towards COVID-19 among student nurses in Manila, Philippines: A cross-sectional study - Earl Zedrick S Quisao; Raven Rose R Tayaba; Gil P Soriano (Belitung Nursing Journal, 2021)
Background: Assessing the current understanding of future health care workers about the COVID-19 is very important in order to identify gaps that affect their perceptions and responses, which they can integrate into the people in the community.Objective: This study aimed to investigate the knowledge, attitude, and practice towards COVID-19 of student nurses in Manila, Philippines.Methods: This study utilized a descriptive cross-sectional survey of 314 individuals from October 2020 to December 2020 to evaluate the association of different factors to knowledge, attitude, and practice towards COVID-19. Frequency, percentage, mean, standard deviation, t-test, and one-way ANOVA were used to analyze the data gathered.Results: The survey revealed that the respondents have a mean knowledge score of 18.76 (SD = 1.64), a mean score for attitude of 26.58 (SD = 2.71) and a mean score for practice of 4.26 (SD = 0.93). A significant different were noted in terms of year level with level 3 having a higher mean score (M = 19.01, F = 2.696, p = 0.046) compared to other levels and type of school, with public university students having a higher level of knowledge (M = 18.97, t = 2.070, p = 0.039). In terms of attitude, females have higher mean scores (M = 26.85, t = -2.630, p = 0.009 and students from public university have higher scores (M = 2.81, t = -4.406, p = 0.000) than students from private university. For practice, a significant difference was noted in terms of year level, with level 3 students having a higher mean score (M = 4.42, F = 3.180, p = 0.024) compared to other year levels.Conclusion: Filipino student nurses have a high level of knowledge about COVID-19 and are mainly optimistic about controlling the pandemic. Nevertheless, having constant reminder from the authorities and health care professionals are the solution to aid public knowledge and comprehension relating to COVID-19.